2019 IEEE 21st International Workshop on Multimedia Signal Processing (MMSP) 2019
DOI: 10.1109/mmsp.2019.8901764
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution of Omnidirectional Images Using Adversarial Learning

Abstract: An omnidirectional image (ODI) enables viewers to look in every direction from a fixed point through a headmounted display providing an immersive experience compared to that of a standard image. Designing immersive virtual reality systems with ODIs is challenging as they require high resolution content. In this paper, we study super-resolution for ODIs and propose an improved generative adversarial network based model which is optimized to handle the artifacts obtained in the spherical observational space. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 30 publications
(51 reference statements)
0
33
0
Order By: Relevance
“…Single-image super-resolution (SISR) aims to enhance the resolution of an image (e.g., 4×). In this work, we propose a novel 360°SISR algorithm that recovers more accurate geometric structures (e.g., characters on the floor) than the state-of-the-arts perspective [4] and 360° [6] SISR algorithms.…”
Section: Ground Truthmentioning
confidence: 99%
See 4 more Smart Citations
“…Single-image super-resolution (SISR) aims to enhance the resolution of an image (e.g., 4×). In this work, we propose a novel 360°SISR algorithm that recovers more accurate geometric structures (e.g., characters on the floor) than the state-of-the-arts perspective [4] and 360° [6] SISR algorithms.…”
Section: Ground Truthmentioning
confidence: 99%
“…the SR network for perspective images can be applied to the 360°domain even with little or no treatment for the projection distortion, a recent study [9] showed that the GAN-based SISR techniques used in [6] tend to degrade the corresponding PSNR values. Therefore, evaluation based on the reconstruction error in [6] has not revealed the effect of the distortionaware treatment for perspective to 360°domain adaption. The goal of this work is to explore the better transfer from the perspective SISR to the 360°SISR.…”
Section: Ground Truthmentioning
confidence: 99%
See 3 more Smart Citations